ACTIVENESS ENHANCEMENT AND STUDENT LEARNING RESULTS THROUGH THE DISCOVERY LEARNING MODEL AND MONOPOLY BOARD GAME MEDIA IN ELEMENTARY CLASS IV - Rico Dwi Kristanto; Stefanus C Relmasira; Agustina Tyas Asri Hardini (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract:This research aims to improve the activeness and learning outcomes of fourth grade elementary school students by applying the Discovery Learning model assisted with the Monopoly Board Game. The research is a Classroom Action Research carried out at Tingkir Tengah 01 Elementary School, with 29 students as research subjects. The data of this research were obtained using test techniques, in the form of questions and non-tests for measuring activeness, teacher and student activities. The result indicates an increase in the activeness and learning outcomes of students in each learning cycle when compared with the initial condition, for student activity it is evidenced by the number of students who are in the active category. Student learning outcomes has also increased in each cycle, it can be seen from a large number of students who achieved passing grades in cycle I and increasing in cycle II. Keywords :Learning Outcomes, Activeness,Discovery Learning, Monopoly Board Game Abstrak: Penelitian yang dilakukan ini bertujuan untuk meningkatkan keaktifan dan hasil belajar siswa kelas IV SD dengan menerapkan model Discovery Learning yang berbantuan dengan media Monopoly Board Game. Penelitian yang dilakukan adalah Penelitian Tindakan Kelas dan dilaksanakan di SD Negeri Tingkir Tengah 01, dengan subjek penelitian sebanyak 29 siswa. Data penelitian ini didapatkan dengan menggunakan teknik tes yaitu berupa soal dan non tes berupa lembar observasi keaktifan, lembar aktivitas guru dan lembar aktivitas siswa. Hasil penelitian ini menunjukkan adanya peningkatan pada keaktifan dan hasil belajar siswa pada setiap siklusnya jika dibandingkan dengan kondisi awal, untuk keaktifan siswa hal tersebut dibuktikan dengan jumlah siswa yang masuk dalam kategori aktif. Data hasil belajar siswa mengalami peningkatan di setiap siklusnya, hal tersebut dapat dilihat dari banyaknya jumlah siswa yang mendapat nilai tuntas pada siklus I dan meningkat di siklus II. KataKunci: Hasil belajar, Keaktifan, Discovery Learning, Monopoly Board Game